Persistence of Seed Dormancy in Superior Rice Varieties across Different Storage Durations - Sulaiman, Amri Farhan; Suroso, Bejo; Wijaya, Insan (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
Varietal differences in dormancy persistence often delay germination, complicating seed quality certification and distribution. This study analyzes the dormancy characteristics and physiological readiness of two superior rice varieties, Inpari 32 and Memberamo, across storage intervals of 2, 3, 4, and 5 weeks post-harvest. The research employed a completely randomized design with eight treatment combinations and three replications. Core methods included standardized testing for germination rate, maximum growth potential, vigor index, and dormancy intensity, along with moisture content analysis. Quantitative results revealed a significant interaction between variety and storage duration: Inpari 32 dissipated dormancy faster, reaching an 88% germination rate by the third week, whereas Memberamo required five weeks to meet the national standard at 87%. Dormancy intensity significantly declined from 29.0% to 2.7% for Inpari 32 and from 66.0% to 8.0% for Memberamo over the five-week period. These findings indicate that Inpari 32 reaches optimal physiological maturity earlier than Memberamo, providing a critical basis for variety-specific storage management and quality testing schedules.